1998
DOI: 10.1088/0022-3727/31/3/011
|View full text |Cite
|
Sign up to set email alerts
|

The spatio-temporal development of electron swarms in gases: moment equation analysis and Hermite polynomial expansion

Abstract: Abstract. Spatio-temporal development of electron swarms in gases is simulated using a propagator method based on a series of one-dimensional spatial moment equations. When the moments up to a suécient order are calculated, the spatial distribution function of electrons, p(x), can be constructed by an expansion technique using Hermite polynomials and the weights of the Hermite components are represented in terms of the electron diãusion coeécients. It is found that the higher order Hermite components tend to z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(49 citation statements)
references
References 27 publications
0
49
0
Order By: Relevance
“…An advantage of the evaluation of distribution shapes with C x;n and C y;n is that the Hermite components have visual shapes; in contrast to this the deånition of the cumulants is abstract. Sugawara et al (1998) demonstrated the convergence of p(x; t) to a Gaussian distribution by means of C x;n in the previous longitudinal analysis. Similar results for p(y; t) can be seen in ågure 8.…”
Section: The Transverse Electron Distribution In Real Spacementioning
confidence: 71%
See 2 more Smart Citations
“…An advantage of the evaluation of distribution shapes with C x;n and C y;n is that the Hermite components have visual shapes; in contrast to this the deånition of the cumulants is abstract. Sugawara et al (1998) demonstrated the convergence of p(x; t) to a Gaussian distribution by means of C x;n in the previous longitudinal analysis. Similar results for p(y; t) can be seen in ågure 8.…”
Section: The Transverse Electron Distribution In Real Spacementioning
confidence: 71%
“…In the previous work (Sugawara et al 1998), two coordinates v and í were necessary to calculate the longitudinal moment distribution m x;n (v; t). Here one may simply integrate m x;n (v; t) with respect to û because electrons with common velocity components (v; í ) are all equivalent in the contribution to the longitudinal moment equations irrespective of û.…”
Section: Moment Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using "n,k and "n,total, Dn,k and Dn,total (n ? : 2) are given as 6 ) Dn,k Figure 2 shows the relations between the moments, cumulants and diffusion coefficients of the component and composite electron swarms. What to be derived is Dn,total = Dn,eq for n ?…”
Section: I: Exp{[x -Gk (T)]q)}jk (X T)dxmentioning
confidence: 99%
“…2 ) discussed the difference between physical models based on eqs. (1) and (2), and pointed out the relationship between D3 and D4 and the skewness and kurtosis of the shape of f. Blevin and n!Dn is the time derivative of the nth-order cumulant Kn of f. 6 ) The cumulant is a statistical quantity representing the deviation of distribution shape from a Gaussian distribution. This fact indicates a mutual dependence between Dn and the shape of f. Here, a question arises.…”
Section: Introductionmentioning
confidence: 99%